Studi Literatur : Luaran Fungsional Pasien Hirshcsprung Pasca Pull-Through Berdasarkan Skor Rintala - Muhammad Arvienji Wardaya; Miftahurrahmah Miftahurrahmah; Esa Indah Ayudia; Willy Hardy Marpaung; Humaryanto Humaryanto; Budi Justitia (Jurnal Litbang Edusaintech, 2022)
Hirschsprung's disease is a disorder that causes interference with the absence of innervation in the colon, causing peristalsis in the colon. Treatment of Hirschsprung performed surgically using the Pull-through method. Data regarding the post-pull-through functional outcome has not been obtained, especially in Indonesia. Using the Rintala score, this study aims to analyze the functional outcome of post-pull-through Hirschsprung patients based on the Rintala score from a literature study. This study used a literature review approach as many as fifteen literature sources from Google Scholar, Pubmed, Science Direct, Elsevier and DOAJ according to the inclusion criteria set by the researcher. Based on the results of the literature study, from 15 literatures there are 14 literature have information about the age, sex, and complications of Hirshscprung patients after the pull-through. And from 15 literatures, all literature has information about post Pull-though evaluation using the Rintala score and the type of Pull-through operation used. Based on the gender of the Hirschsprung patient, it was more common in boys, the age at evaluation ranged from 3 to 11 years. Post pull-through complications are enterocolitis, anastomotic stricture, and constipation. The results of the Rintala scoring show that the interpretation of "continence is good" in all the literature and most of the literature uses the TEPT technique. Keyword:Hirschsprung Disease, Pull-through, Rintala Score ABSTRAK Penyakit Hirschsprung merupakan kelainan yang ditandai dengan tidak adanya persarafan pada kolon sehingga menyebabkan gangguan peristaltik pada kolon. Penanganan Hirschsprung dilakukan pembedahan dengan metode Pull-through. Data mengenai hasil luaran fungsional pasca pull-through belum banyak didapatkan terutama di Indonesia Dengan menggunakan skor Rintala, penelitian ini bertujuan untuk menganalisis luaran fungsional pasien Hirschsprung pasca Pull-through berdasarkan skor Rintala dari studi literatur. Penelitian ini menggunakan pendekatan studi literatur sebanyak lima belas sumber literatur yang diperoleh dari mesin pencari Google Scholar, Pubmed, Science Direct, Elsevier dan DOAJ sesuai dengan kriteria inklusi yang telah ditetapkan peneliti. Berdasarkan hasil studi literatur, dari 15 literatur terdapat 14 literatur yang memiliki informasi mengenai usia, jenis kelamin, dan komplikasi pasien Hirshscprung pasca pull-through. Kemudian, dari 15 literatur, semua literatur memiliki informasi mengenai evaluasi pasca Pull-though menggunakan skor Rintala serta jenis operasi Pull-through yang digunakan. Berdasarkan jenis kelamin pasien Hirschsprung lebih banyak terjadi pada anak laki, usia saat evaluasi berkisar 3-11 tahun. Komplikasi pasca Pull-through ditemukan berupa enterokolitis, striktura anastomosis, dan Konstipasi. Skoring rintala didapatkan hasil interpretasi “kontinensia Baik” di semua literatur dan sebagian besar literatur menggunakan teknik TEPT Kata kunci: Hirschsprung, Pull-through, Skor Rintala